2018
DOI: 10.1007/978-1-4939-7601-0_1
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA

Abstract: MicroRNAs (miRNAs), widely distributed, small regulatory RNA genes, target both messenger RNA (mRNA) degradation and suppression of protein translation based on sequence complementarity between the miRNA and its targeted mRNA. Different names have been used to describe various types of miRNA. During evolution, RNA retroviruses or transgenes invaded the eukaryotic genome and were inserted itself in the noncoding regions of DNA, conceivably acting as transposon-like jumping genes, providing defense from viral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 156 publications
0
15
0
Order By: Relevance
“…MiRNAs are a class of small non‐coding RNAs of ~22 nt that suppress gene expression by hybridizing to the 3' untranslated region of messenger RNA (mRNA), promoting mRNA degradation or disrupting translation, thus acting as post‐transcriptional regulators, repressing, or completely silencing, protein translation. Several miRNAs are strongly up‐regulated during pathological stress, and they appear to be aberrantly expressed in blood plasma or serum during the course of many diseases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are a class of small non‐coding RNAs of ~22 nt that suppress gene expression by hybridizing to the 3' untranslated region of messenger RNA (mRNA), promoting mRNA degradation or disrupting translation, thus acting as post‐transcriptional regulators, repressing, or completely silencing, protein translation. Several miRNAs are strongly up‐regulated during pathological stress, and they appear to be aberrantly expressed in blood plasma or serum during the course of many diseases …”
Section: Introductionmentioning
confidence: 99%
“…Among the plethora of miRNAs progressively annotated (about 1500‐2000 human miRNAs have been identified), some miRNAs have been demonstrated to play a significant role in cardiogenesis, heart function and pathology, thus contributing to the progression of cardiovascular diseases such as cardiac hypertrophy and fibrosis and myocardial infarction . Cardiac miRNAs such as miR‐1, miR‐133a, miR‐208a/b and miR‐499 are abundantly expressed in the myocardium and are present, stable and detectable in the circulation in different cardiovascular events, such as early after myocardial infarction . MiRNAs have also been explored for cardiovascular risk stratification, thus assuming an increasingly important role as potential cardiovascular biomarkers…”
Section: Introductionmentioning
confidence: 99%
“…Dicer1 is an RNaseIII endonuclease that cleaves precursor microRNAs into double-stranded miRNA duplex during miRNA biogenesis. [ 6 ] After unwinding, mature active miRNA subsequently binds to downstream target genes and regulates their expression through transcriptional silencing or mRNA degradation. [ 6 ] Somatic DICER1 mutations, particularly those within the RNase IIIb domain, may lead to improperly cleaved 5p miRNA from precursor microRNA hairpin structures and complete loss of Dicer1 protein function.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] After unwinding, mature active miRNA subsequently binds to downstream target genes and regulates their expression through transcriptional silencing or mRNA degradation. [ 6 ] Somatic DICER1 mutations, particularly those within the RNase IIIb domain, may lead to improperly cleaved 5p miRNA from precursor microRNA hairpin structures and complete loss of Dicer1 protein function. [ 7 , 8 ] Although many carriers of germline DICER1 mutations remain unaffected, previous studies have shown that most DICER1 syndrome tumors have 1 allele with somatic missense DICER1 mutations within 5 known hotspots in the RNase IIIb domain.…”
Section: Introductionmentioning
confidence: 99%
“…ncRNA is transcribed from a DNA sequence that is also considered a RNA gene; these types of RNA are transcribed directly by type III RNA polymerases or processed indirectly from a large transcript of type II RNA polymerases. Examples of ncRNAs include transfer RNA, nucleolar RNA, nuclear RNA, phage RNA and viral RNA [1]. A type of small, single-stranded RNA that possesses the reverse complement of the mRNA transcript of another protein coding gene is called microRNA (miRNA).…”
Section: Introductionmentioning
confidence: 99%